Establishment and Characterization of Brain Cancer Primary Cell Cultures From Patients to Enable Phenotypic Screening for New Drugs - dePadua, Michelle; Kulothungan, Preethi; Lath, Rahul; Prasad, Ravikanti; Madamchetty, Kranthi; Atmakuri, Shravya; Ragamouni, Sravanthi; Gandhari, Mukesh; Khandrika, Lakshmipathi; Jain, Jugnu (Frontiers in Pharmacology, 2022)
Aim: Desmoplastic infantile ganglioglioma (DIG), is a rare tumor arising mainly during the first two years of life. Molecular characterization of these benign yet rapidly proliferating tumors has been limited to evaluating a few mutations in few genes. Our aim was to establish a live cell culture to enable the understanding of the cellular processes driving the non-malignant growth of these tumors. Methods: Tumor tissue from a rare non-infantile 8-year-old female DIG patient was dissociated and digested using collagenase to establish live cultures. Both 2D monolayer and 3D neurospheres were successfully cultured and characterized for proliferative potential and immortal phenotype, intrinsic plasticity, presence of cancer stem cells and the expression of stem cell markers. Cells cultured as 3D were embedded as tissue blocks. Immunohistochemistry was performed in both tissue and 3D sections for markers including synaptophysin, vimentin, neurofilament and MIB-1. Mutation analysis by NGS was performed using Bioserve-100 panel. Results: Using immunohistochemistry, the 3D cultures were shown to express markers as in the original DIG tumor tissue indicating that the spheroid cultures were able to maintain the heterogeneity found in the original tumor. Cells continued proliferating past passage 10 indicative of immortalization. Enrichment of cancer stem cells was observed in neurospheres by FACS using CD133 antibody and RT-PCR. Mutation analysis indicated the presence of germline mutations in three genes and somatic mutations in two other genes. Conclusions: A spontaneous cell line-like cell culture with high percentage of stem cells has been established from a DIG tumor for the first time.